2011
DOI: 10.5897/ajb10.1076
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant responses of lentil and barley plants to boron toxicity under different nitrogen sources

Abstract: In this study, the effects of different nitrogen sources on lentil (Lens clunaris) and barley (Hordeum vulgare) plants, exposed to 5 and 10 mM boron stress previously, were studied. After ten-day germination, the lentil (native) and barley (Tokak157/37) were incubated 16 h light and 8 h dark per day for 7-day growth cycle under the conditions of boron stress via different nitrogen sources (10 mM nitrogen in NH 4 Cl, KNO 3 and urea). As a result of the changes in the nitrogen sources of the plants, there were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Excess of boron interferes in nitrate reductase activity and thus affect the synthesis of amino acids [28], in special glutamic acid that can lead to imbalance in chlorophyll production once this molecule is synthesised from alpha-aminolevulinic acid, derived from glutamic acid. So, as we did not find any effects in chlorophyll content we could assume that it had no effect on nitrogen metabolism, although we showed some opposite results for other plants in another study [29]. In that work, nitrogen sources were evaluated to overcome B toxicity in lentil and barley plants and the authors found a decrease in chlorophyll content in both species.…”
Section: Boron Effects On Photosynthetic Pigments and Nitrogenous Commentioning
confidence: 66%
“…Excess of boron interferes in nitrate reductase activity and thus affect the synthesis of amino acids [28], in special glutamic acid that can lead to imbalance in chlorophyll production once this molecule is synthesised from alpha-aminolevulinic acid, derived from glutamic acid. So, as we did not find any effects in chlorophyll content we could assume that it had no effect on nitrogen metabolism, although we showed some opposite results for other plants in another study [29]. In that work, nitrogen sources were evaluated to overcome B toxicity in lentil and barley plants and the authors found a decrease in chlorophyll content in both species.…”
Section: Boron Effects On Photosynthetic Pigments and Nitrogenous Commentioning
confidence: 66%
“…The chlorophylls are responsible to the photochemical and biochemical reactions during light capitation [61], while carotenoids present an important role related to photoprotection against excessive sunlight [62], given that both pigments work simultaneously into photosynthetic machinery [63]. However, the excessive B supply represents a problem to photosynthetic pigments, with consequent decrease in chlorophylls [64][65].…”
Section: Zinc Toxicity and Silicon Benefits On Photosynthetic Pigmentsmentioning
confidence: 99%